The Significance of the Banda Sea: Tectonic Deformation Review in Eastern Sulawesi - Titu-Eki, Adept; Hall, Robert (Geological Agency, 2020)
DOI:10.17014/ijog.7.3.291-303The geology of eastern Sulawesi is widely known for its complexity due to multiple deformation stages.The geology on land has been studied excessively, but little assessment has been made on the offshore geology, thus the geological evolution of the area remains a subject of controversy. A thorough observation of high multibeam bathymetry dataset offshore and SRTM dataset onshore provides an understanding on the geological features relating to the tectonic deformation. Exquisite morphological features include carbonate buildups and gravitational collapse dominating the shelf areas whereas distinct form of ridges and seamount exists in the offshore. Structural features in this area including the major Tolo Thrust and South Sula Fault varied structural lineations on land with several polygonal extensional faulting and accretionary wedge on the west of the North Banda Sea. The existence of these features may indicate that the area was majorly deformed during Neogene, specifically relating to the opening of the Banda Sea due to the subduction rollback of Banda.